Reliability of intraoperative radiographic visual assessment of the hallux interphalangeal angle after hallux valgus correction - Norberto Faria Ferrao, Paulo; Pandelis Saragas, Nikiforos; Khademi, Mohammadali (Journal of the Foot & Ankle, 2022)
Objective: The aim of this study was to evaluate the reliability and reproducibility of visual estimation of the hallux interphalangeal angle (IPA). As a secondary aim we assessed for change in the IPA before and after hallux valgus (HV) correction. Methods: A total of 50 surgically treated HV deformities were included in the study. Two surgeons visually estimated the IPA on intraoperative fluoroscopy after correcting HV. The fellow then measured the IPA formally on a printout of the fluoroscopic image. Pre-and intraoperative HVI angles were compared to assess for change after HV correction. Results: The researchers found the interobserver reliability of radiographic visual assessment of the IPA to be 78% and intraobserver reliability to be 76% and 80% for surgeon 1 and 2, respectively. It was found that the preoperative IPA is on average 5.5 degrees less than IPA after HV correction. Conclusion: Radiographic visual assessment of the IPA of the hallux was found to be reliable intraoperatively, thus aiding in the amount of correction required by Akin osteotomy. HVI can be masked by hallux pronation in HV deformity and should be assessed intraoperatively after HV correction. Level of Evidence II; Therapeutic Studies; Prospective Comparative Study.